1976
DOI: 10.1113/jphysiol.1976.sp011275
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caffeine and tetracaine on the time course of potassium contractures of single muscle fibres.

Abstract: SUMMARY1. The time course of potassium contractures can be significantly prolonged by low concentrations of caffeine.2. This effect of caffeine is not due to impairment of the fibre relaxing system.3. Under conditions where contractile repriming is delayed (low temperature) an extra amount of activator can be released by caffeine, in addition to that released by potassium.4. The source of this extra amount of activator is intracellular since its release can be shown in a 0 calcium EGTA medium.5. Local anaesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
101
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(117 citation statements)
references
References 25 publications
15
101
1
Order By: Relevance
“…A similar effect of 0.5 mM Ni2+ was observed on the long term effect of Ca2+ reduction (not shown here). These results agree with those of CAPUTO (1972CAPUTO ( , 1981, who indicated that Ni2+ can substitute for Ca2+ in excitation-contraction coupling (E-C coupling). Corresponding to the 5 and 10 mM Mg2+, 1 and 3 mM Ni2+ in low Ca2+ solution markedly inhibited the peak tensions of both components (Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…A similar effect of 0.5 mM Ni2+ was observed on the long term effect of Ca2+ reduction (not shown here). These results agree with those of CAPUTO (1972CAPUTO ( , 1981, who indicated that Ni2+ can substitute for Ca2+ in excitation-contraction coupling (E-C coupling). Corresponding to the 5 and 10 mM Mg2+, 1 and 3 mM Ni2+ in low Ca2+ solution markedly inhibited the peak tensions of both components (Fig.…”
Section: Resultssupporting
confidence: 92%
“…CAPUTO (1981) assumed that external Ca2+ stabilizes one of the steps of E-C coupling that regulates Ca release from the SR. The results of CAPUTO (1972CAPUTO ( , 1981 and our present data indicate that Ni2+ can substitute for external Ca2+ in developing tension and in maintaining a normal time course of the secondary component (Fig. 4) and suggest that at least Ca influx (BIANCHI and SHANES, 1959;BIANCHI, 1968) or a slow inward Ca current (BEATY and STEFANI, 1976;STANFIELD, 1977;SANCHEZ and STEFANI, 1978) may be excluded from the possible mechanisms of the direct effect of external Ca2+ on K contractures STEFANI, 1981, 1982).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations